"Ni‐Less" Cathodes for High Energy Density, Intermediate Temperature Na–NiCl2 Batteries. Issue 10 (8th March 2018) - Chang, Hee‐Jung; Lu, Xiaochuan; Bonnett, Jeffery F.; Canfield, Nathan L.; Son, Sori; Park, Yoon‐Cheol; Jung, Keeyoung; Sprenkle, Vincent L.; Li, Guosheng
Abstract: Among various battery technologies being considered for stationary energy storage applications, sodium–metal halide (Na–MH) batteries have become one of the most attractive candidates because of the abundance of raw materials, long cycle life, high energy density, and superior safety. However, one of issues limiting its practical application is the relatively expensive nickel (Ni) used in the cathode. In the present work, the focus is on efforts to develop new Ni‐based cathodes, and it is demonstrated that a much higher specific energy density of 405 Wh kg −1 (16% higher than state‐of‐the‐art Na–MH batteries) can be achieved at an operating temperature of 190 °C. Furthermore, 15% less Ni is used in the new cathode formula than that in conventional Na–NiCl2 batteries. Long‐term cycling tests also show stable electrochemical performance for over 300 cycles with excellent capacity retention (≈100%). The results in this work indicate that these advances can significantly reduce the raw material cost associated with Ni (a 31% reduction) and promote practical applications of Na–MH battery technologies in stationary energy storage systems. Abstract : "Ni‐less" cathode is prepared and tested for the first time to demonstrate high energy density Na–NiCl2 batteries at an operating temperature of 190 °C. The energy density of "Ni‐less" cell reaches 405 Wh kg −1 with excellent capacity retention after 300 cycles, making Na–NiCl2 batteries more competitive for stationary energy storage application.